Data Mining is used in Education System - Venkataratnam, B; Sravanthi, G; Deepa, C (International Journal of Computer Sciences and Engineering, 2018)
Data mining is the process of sorting through large datasets to identify patterns and establish the relationship to solve problems through data analysis. Data mining tools allows enterprises to predict future trends. One of the prominent applications of data mining tools is in the field of education. Educational data mining, also known as EDM is an emerging, multidisciplinary area of research, concerned with studying and analyzing data from various educational databases. It helps in extracting meaningful information from large repositories using various data mining methods to enable data-driven decision making for improving the current educational practice. One of the biggest challenges faced by higher education today is predicting the paths of students. Data mining is a better tool to predict the results of the student. Educational Data Mining (EDM) helps in a big way to answer the issues of predictions and profiling of not only the students but other stake holders of education sectors. Thispaper focus on using various data mining tools like Association, Clustering, and Decision tree to analyze the large volume of data stored in the University databases to track the academic results of the students.